THE IMPACT OF GAMIFICATION ON REPURCHASE INTENTION: MEDIATING ROLE OF PERCEIVED ENJOYMENT AND MODERATING ROLE OF REWARD SATISFACTION - Natalia, Erica Destiani; Gabriella, Annette; Adrie Oktavio (Universitas Nahdlatul Ulama Surabaya, 2025)
The advancement of technology has brought a significant impact to the tourism industry, marked by the rise of Online Travel Agents (OTAs) that assist consumers in planning their trips. Traveloka ranked first as the most popular OTA, followed by Tiket.com and Agoda. In an effort to attract and retain customers, Traveloka has integrated gamification features that encourage repeat transactions by offering rewards such as points that can be redeemed for vouchers. This study examines the Influence of gamification on repurchase intention, with perceived enjoyment serving as a mediator and reward satisfaction functioning as a moderator. Data was collected from 201 Traveloka users who had made a transaction and engaged with the gamification features within the last six months. Using purposive sampling and a quantitative research approach, the study employed structural equation modeling (SEM) for data analysis. The findings found that gamification significantly influences repurchase intention and enhances perceived enjoyment. Additionally, perceived enjoyment partially mediates the relationship between gamification and repurchase intention. Meanwhile, reward satisfaction, as a moderating variable, weakens the relationship between gamification and repurchase intention. These results offer valuable insights into the effectiveness of gamification strategies for customer engagement and repeat purchase behavior in the highly competitive OTA market.